Management of Syndesmotic Ankle Injuries: Results of a Survey of Pediatric Orthopaedic Society of North America Members - Caroline E. Williams, MD; Blair Stewig, BS; Sang Won Lee, MS; Danielle Cook, MA; Benjamin J. Shore, MD, MPH, FRCSC; Collin J. May, MD, MPH (Elsevier, 2024)
Background: Although utilization of dynamic suture-button fixation for adult syndesmotic injuries has shown improved outcomes over static screw fixation, data in pediatric populations is limited. This study evaluated trends in management and identified factors influencing surgeon choice of implant for pediatric syndesmotic injuries. Methods: The Pediatric Orthopaedic Society of North America (POSNA) members were surveyed regarding syndesmotic injury implant preferences between October 2021 and May 2022. Respondents that opted out, treated <1 syndesmotic ankle injury in the past year, or had conflicting financial obligations were excluded. Results were summarized and analyzed using logistic regression to assess for significance between years posttraining and technique preference. Odds ratios (OR) and 95% confidence intervals (CI) were calculated for significance (P-values<.05). Results: Among 103 respondents to the survey (with 102 complete responses), 25% were <5 years posttraining, 24% between 5 and 10 years, 21% between 11 and 15 years, and 28% ​> ​15 years posttraining. Twenty-four percent (24/102) preferred screw versus 76% (78/102) preferring suture-button implants for syndesmotic injuries. Members >15 years posttraining were 4.7 times more likely to prefer screw implants compared to members <5 years posttraining (OR ​= ​4.7; 95% CI, 1.14-19.34; P ​= ​.03). Since starting their clinical practice, 62 respondents (60%) reported an implant preference change, with avoidance of secondary surgery (46/62; 74%) and extrapolation from adult outcomes (39/62; 63%) cited as primary motivating factors. Of the 40 members with no preference change, comfort with the procedure was the primary cited reason (33/40; 83%). Among those choosing operative intervention, radiograph-based cases showed preference for the suture-button in 70%-79% of respondents for skeletally mature patients versus 71%-81% for skeletally immature patients. Conclusions: Our data shows that the shift over time from screw to suture-button implant fixation for pediatric and adolescent syndesmotic ankle injuries is largely due to interest in avoiding implant removal and extrapolation from superior outcomes seen with suture-button use in adults. Larger comparative studies of pediatric and adolescent patients treated with suture-button versus screw fixation are needed to establish standards of care for these challenging injuries. Key Concepts: (1) Literature for operative syndesmotic injury management in adults has shown improved outcomes of dynamic suture-button fixation over static screw fixation, but data in pediatric and adolescent populations is limited. (2) A survey of 102 POSNA members shows that 76% prefer suture-button, 24% prefer screw fixation with members >15 years posttraining 4.7 times more likely to prefer screw fixation to members <5 years posttraining. (3) Among 62 respondents who switched implant preference during their clinical practice, avoidance of secondary surgery and extrapolation from outcomes in adults were the two most cited reasons. (4) Among 40 respondents who did not switch implant preference, comfort with the procedure was the most cited reason. (5) Comparative studies of suture-button versus screw implants for treatment of pediatric and adolescent syndesmotic ankle injuries are needed to establish an evidence-based standard of care management. Level of Evidence: Level V: Expert Opinion